2009
DOI: 10.1002/mame.200800214
|View full text |Cite
|
Sign up to set email alerts
|

Melt Mixing of Ethylene/Butyl Acrylate/Glycidyl Methacrylate Terpolymers with LDPE and PET

Abstract: The chemical modification by melt‐mixing of an EBAGMA terpolymer with LDPE and PET was investigated with the aim to use these EBAGMA/LDPE and EBAGMA/PET blends (in equal weight quantities) as compatibilizer master batches to improve the compatibility of the LDPE/PET system. It is shown that when the EBAGMA terpolymer is melt blended with LDPE, almost 40% of the initial amount of EBAGMA is linked to the LDPE backbone. In contrast, in the case of EBAGMA/PET, FT‐IR spectra indicate the total reactivity between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The compatibilization of the PLA30TPU blend with EBG seemed to increase the SS domain thermal stability, considering that the other two decomposition peaks at 409 °C ( T dmax3) and 470 °C ( T dmax4 ) had a mass loss of about 15% and that the EBG content in this blend was 5 wt %. In their study on blends of low‐density polyethylene/PET compatibilized by EBG, Benhamida et al . attributed the last two decomposition temperatures to the thermal decomposition of EBG.…”
Section: Resultsmentioning
confidence: 99%
“…The compatibilization of the PLA30TPU blend with EBG seemed to increase the SS domain thermal stability, considering that the other two decomposition peaks at 409 °C ( T dmax3) and 470 °C ( T dmax4 ) had a mass loss of about 15% and that the EBG content in this blend was 5 wt %. In their study on blends of low‐density polyethylene/PET compatibilized by EBG, Benhamida et al . attributed the last two decomposition temperatures to the thermal decomposition of EBG.…”
Section: Resultsmentioning
confidence: 99%
“…PET showed clear diffraction patterns at 16.4°, 17.7°, 22.8°, 26.2° for the corresponding crystal planes of (0 −1 1), (0 1 0), (1 −1 0), and (−1 0 3) . In addition, the characteristic diffraction peaks of 21.6° and 24° were corresponding to the HDPE orthorhombic crystal plane (110) and (200), respectively, in combination with a broad amorphous halo . For PET/N‐HDPE composites, the major diffraction peak remained unchanged, except for the observed NIR diffraction peaks at 27.4° (110), 36.0° (101), 54.2° (211), and the decreased intensity of diffraction peaks for PET with increasing HDPE contents (omitted for brevity).…”
Section: Resultsmentioning
confidence: 98%
“…However, in comparison with blends containing MB1, the SEM micrographs of LDPE/PET/MB2 exhibit small domains of PET dispersed in LDPE matrix, with almost 5 mm size. According to our previous work, [15] this morphology could be explained by the fact that GMA groups have already reacted with PET during the preparation of MB2. Indeed, the extraction tests showed that no EBAGMA was extracted, indicating total reactivity of EBAGMA with PET through the reaction of the epoxy group of EBAGMA terpolymer with the hydroxyl and COOH groups of PET during MB2 preparation.…”
Section: Resultsmentioning
confidence: 99%
“…This could cause EBAGMA molecules to preferentially orient at the LDPE surface such that the polar part of EBAGMA would stay on the surface and the non-polar part will be diffused inside the LDPE. [15] When PET is added, such an orientation of EBAGMA would facilitate the interactions between PET and GMA right at LDPE/PET interface, [3] as observed in the study of the morphology by SEM exhibiting a finer dispersion of PET in the LDPE matrix.…”
Section: Tensile Testsmentioning
confidence: 99%
See 1 more Smart Citation